“Analisis Wacana Pesan Dakwah Dalam Film I-Tanggang: Mother Of All Lies” - Dettia Herlinda; Penmardianto Penmardianto (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The film I-Tanggang: Mother of Lies tells the story of a disobedient child and a mother who lies, causing extreme conflict in 3 family stories that are told and have 12 episodes. It is important to explain that da'wah messages can be conveyed through various media, one of which is film media, so that when watching a film you don't just enjoy the storyline. But, also da'wah messages which are of course very useful. Thus, the researcher wants to review and describe the preaching message contained in the film I-Tanggang: Mother of All Lies. The problems to be uncovered in this study are: the macro discourse structure, the superstructure and the micro structure of the dakwah messages contained in the dialogue texts of the film characters I-Tanggang: Mother of Lies in the story of the character Syafiq. The type of research that the researchers used was a qualitative approach, collecting data through text observation and documentation, while the data analysis technique used was media text analysis using the Teun A. Van Dijk discourse analysis model. Based on the results of the research that the writer did, in the film I-Tanggang: Mother of All Lies, which tells the story of one of the main characters, namely the character Syafiq, there is a da'wah message about faith. (about reciting basmallah and surrendering to Allah SWT.), about sharia (punishment for those who commit adultery and the wife's obedience to her husband), and morals (about hard work and responsibility). The general theme in the film I-Tanggang: Mother Of All Lies is about a syndrome where sufferers always lie and manipulate circumstances, about the important role of parents in educating children, and how a teenager's patience in facing difficulties. life and the twists and turns of problems that he shouldn't have experienced, with mixed storylines (forward and backward plots).